Monoglycoconjugated water-soluble phthalocyanines. Design and synthesis of potential selectively targeting PDT photosensitisers - Zorlu, Yunus; Dumoulin, Fabienne; Bouchu, Denis; Ahsen, Vefa; Lafont, Dominique (Pergamon-Elsevier Science Ltd, 2010)
A series of asymmetrically substituted phthalocyanines conjugated to four different carbohydrate units has been designed to be used as photosensitisers for potential selective recognition by targeted cells. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Water-soluble; Click chemistry; Carbohydrate; Glycerol; Targeting photosensitiser